The Muslims Conquest of Egypt (21HA-642AD) In the Works of Abdel Moneim Majeed presentation: criticism and analysis - Manit, Alahan; Al-Dulaimi, Zakia (Al-Adab Journal, 2024)
A historians is serious task, especially when his or her subject requires analysis of historical events. Some historians are characterizedby objectivity, honesty, and accuracy. They investigate historical material and study it in depth so that they can pass their judgment based on deep knowledge and perceptive approach. Some of them are influenced by mainstream cultures and certain intellectual trends, which put the historical material at risk of inaccuracy, honesty and deviation from the methodology of historical research. The harm of this approach is extremely severe especially when the writer or historian has high scholarly status. Therefore, due to the importance of this issue, the writings of Abdel Moneim Maged, one of the most prominent modern Egyptian historians, who had a diverse and significant output in Islamic history, were selected for evaluation in this study.